“The Translation Cuddles up to the Original Like the Sheep to the Wolf” Nobel Prize Winner Elfriede Jelinek as a Translator - Wolf, Michaela (TTR)

(untitled) (Association canadienne de traductologie, 2012)
Elfriede Jelinek’s stance towards translation is full of respect: her own experiences as a translator showed her that what she primarily did was “learning by doing.” Jelinek has produced about a dozen translations from English and French into German, mostly drama texts. As an author, she became famous for the innovative and provocative language with which she denounces patriarchal structures, the enduring oppression of women, and the insidious continuation of fascist ideology in Austria and other parts of Europe. Yet her model of literature bluntly opposes her model of translation. She has repeatedly said that as a translator she supports “basically the method of relatively literal translation”—a claim which can be easily proved by looking at her translations.In my paper I will first give an overview of Jelinek’s translations (some of which are co-productions with other translators) and present her own views on translation, which will show that she is very much aware of the pitfalls of the translation activity. I will then analyze Jelinek’s notion of translation, followed by a short analysis of her translation of Christopher Marlowe’s The Jew of Malta. This will be the basis for my discussion of whether her ideas on translation, as expressed in several interviews and speeches, have been put into practice in her translation. It is, however, my assumption that Jelinek does not follow a strict set of translation strategies; rather, she engages intuitively with every new translation project.